The dual benefits of comic reading: Enhancing mental health and language learning - Wahyuni, Erly; Wajdi, Majid; Susanto, Budi; Sanjaya, I Nyoman Suka; Sahoo, Parshuram (Journal of Language, Literature, Social and Cultural Studies, 2025)
This study examines how comic reading enhances mental health and English language skills by exploring its role in stress reduction, emotional well-being, and language acquisition. It focuses on the dual benefits comics offer as therapeutic tools for emotional processing and as effective resources for improving vocabulary, comprehension, and cultural understanding in English learners. Method. A mixed-method approach was adopted, combining survey responses from 100 participants and semi-structured interviews with 15 individuals. Quantitative data were analysed to identify trends in mental health and language improvements, while qualitative data provided deeper insights into personal experiences with comic reading. Results and Discussion. The findings revealed that 75% of participants experienced stress relief from comic reading, with 50% noting improved mood. Emotional connections to characters fostered empathy and self-reflection, aiding in resilience. In language learning, 70% of English learners reported better vocabulary retention and comprehension, highlighting the role of visual cues and narrative context in supporting language acquisition. Challenges such as time constraints and limited research on specific genres were identified, but comics consistently proved to be engaging tools for personal and linguistic growth. Conclusion. Comics are valuable resources for enhancing emotional well-being and language proficiency. Their integration into mental health programs and educational curricula can foster resilience and cultural understanding while providing an enjoyable learning experience. This study underscores the potential of comics as a versatile medium that bridges the gap between entertainment, education, and emotional health.